Role of Concha Bullosa in Chronic Rhinosinusitis - Tiwari, Rashi (Indian J Otolaryngol Head Neck Surg, 2018)
Concha bullosa is one of the most common anatomical variant found in the patients of chronic rhinosinusitis. To study the role of concha bullosa in patients of chronic rhinosinusitis a prospective cross sectional study was done comprising of 60 patients who were having symptoms of sinusitis for more than 12 weeks. These were evaluated with the help of nasal endoscope and CT scan. DNS and concha bullosa are the most common anatomical variant seen in the patients of chronic rhinosinusitis with percentage being 88.3% and 76.6% respectively. Patients with deviated nasal septum and large concha bullosa (bulbous and extensive) were associated with higher incidence of ostiomeatal complex obstruction. There seems a strong relationship between unilateral concha bullosa and contralateral deviated nasal septum in development of chronic rhinosinusitis. (1) To find out the percentage and role of concha bullosa in patients of chronic rhinosinusitis. (2) To screen the patients of chronic rhinosinusitis for concha bullosa. (3) To do the nasal endoscopy and CT scan of the screened patients. Study design: cross sectional study. Sample size: 60. Inclusion criteria: all patients of chronic rhinosinusitis. Exclusion criteria: patients with previous sinus surgeries, malignancy and acute cases of chronic rhinosinusitis.